Effect of form errors on the positioning precision of over-constrained systems. Issue 1 (2019) - Teissandier, Denis; Ledoux, Yann; Arroyave-Tobon, Santiago; Delos, Vincent; Linares, Jean Marc
Abstract: This paper analyses the influence of form deviations on over-constrained mechanical systems. A mechanical clamp was equipped with LVDT sensors to measure relative displacements between its two parts to derive their relative position. Each part was measured using CMM filtering its form deviations. Part feature variations (position, orientation and dimension) and assembly clearances were aggregated on a set of 6d linear constraints. From the measured local displacements another polytope is derived. These two polytopes are compared to quantify the influence of form error on the geometrical behaviour of the assembly. To do this evaluation new metrics are presented and discussed.